2020
DOI: 10.1016/j.cell.2020.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Potent Neutralizing Antibodies against SARS-CoV-2 Identified by High-Throughput Single-Cell Sequencing of Convalescent Patients’ B Cells

Abstract: Highlights d 8,558 IgG1 + antigen-binding clonotypes were identified by high-throughput scRNA/VDJ-seq d 14 potent SARS-CoV-2 neutralizing antibodies were found from 60 convalescent patients d BD-368-2 showed high therapeutic and prophylactic efficacy in SARS-CoV-2-infected mice d Neutralizing antibodies can be directly selected based on predicted CDR3 H structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
1,424
2
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,239 publications
(1,539 citation statements)
references
References 78 publications
67
1,424
2
14
Order By: Relevance
“…While all cryo-EM structural studies to date on SARS-CoV-2 Spike have identified only the "closed" or "one-up" RBD conformation (Cao et al, 2020;Pinto et al, 2020;Walls et al, 2020;Wrapp, Wang, et al, 2020), our split reporter assay identified a population of Spike in "two-up" or "three-up" conformation. The relative population of these RBD conformers and whether they exist in an ACE2-unbound state or emerge only upon ACE2 binding remains unknown ( Figure 6F).…”
Section: Discussionmentioning
confidence: 61%
“…While all cryo-EM structural studies to date on SARS-CoV-2 Spike have identified only the "closed" or "one-up" RBD conformation (Cao et al, 2020;Pinto et al, 2020;Walls et al, 2020;Wrapp, Wang, et al, 2020), our split reporter assay identified a population of Spike in "two-up" or "three-up" conformation. The relative population of these RBD conformers and whether they exist in an ACE2-unbound state or emerge only upon ACE2 binding remains unknown ( Figure 6F).…”
Section: Discussionmentioning
confidence: 61%
“…Of 294 RBD-targeting antibodies, 10% are encoded by IGHV3-53, as compared to only 0.5% to 2.6% in the repertoire of naïve healthy individuals ( 29 ) with a mean of 1.8% ( 30 ). The prevalence of IGHV3-53 in the antibody response in SARS-CoV-2 patients has also been recognized in some recent antibody studies ( 20, 22, 27 ). These observations indicate that IGHV3-53 represents a frequent and public antibody response to the SARS-CoV-2 RBD.…”
Section: Mainmentioning
confidence: 67%
“…Experimentally validated computational docking shows that five of them occupy the ACE2 binding site on the RBD, thus likely achieving direct inhibition of virus-ACE2 interaction. The binding sites of antibody BD368-2 18 and B38 55 also overlap with the RBD ACE2 binding interface. Interestingly, our antibody STE73-2G8 which has subnanomolar EC50 to RBD and potent inhibition and neutralization, binds to the N-terminal part of RBD, away from the ACE2 interface.…”
Section: Discussionmentioning
confidence: 97%